Transforming Energy Systems, Transforming Social Science: Social Researchers and Collective Experimentation in Action - Stasik, Agata; Dańkowska, Alicja; Niedziółka, Tomasz; Dembek, Agata (Stan Rzeczy, 2025)
The accelerating climate change and biodiversity crisis necessitate an unprecedented mobilisation of resources for a sustainable transition. This article explores how the anticipated contribution of social science to this transition requires a redefinition of social researchers’ roles. Drawing on sustainable transition studies, actor–network theory’s concept of translation, and insights from a transdisciplinary research project supporting stakeholder-driven solutions, we offer recommendations for researchers engaged in similar endeavours. We demonstrate how the need for simultaneous modifications of attitudes, interests, institutions, and infrastructure within sustainable solutions also applies to the organisation of scientific research itself.